Space-time analysis of unhealthy food advertising: New Zealand children's exposure and health policy options. (13th August 2019) - Liu, Wei; Barr, Michelle; Pearson, Amber L; Chambers, Tim; Pfeiffer, Karin A; Smith, Moira; Signal, Louise
Abstract: Reducing children's exposure to unhealthy food advertising is an accepted strategy to end childhood obesity. This study aimed to (i) measure children's space-time exposures to unhealthy food advertising in public outdoor spaces, using GPS and wearable cameras; and (ii) test effectiveness of banning options. We compiled data (collected July 2014—June 2015) on 138 12-year-old children in Wellington, New Zealand, using wearable cameras and GPS devices worn over 4 days. In 2017–18, we linked 59 150 images taken in public outdoor spaces to GPS data. Of these, 1631 contained unhealthy food advertising exposures, defined as ≥50% of an advertisement observed in each image. We examined spatial patterns using kernel density mapping and graphed space-time trends. We interpolated a kriged exposure rate across Wellington to estimate exposure reductions for potential bans. Children were exposed to 7.4 (95% CI 7.0–7.8) unhealthy food advertisements/hour spent in outdoor public spaces. Exposures occurred in shopping centres, residential areas and sports facilities, commonly involving fast food, sugary drinks and ice cream. Peak exposure times were weekend afternoons/evenings and weekdays before/after school. In Wellington, we estimated that banning such advertising within 400 m of playgrounds would yield a 33% reduction in exposure, followed by in residential areas (27%), within 400 m of schools (25%), and 50% for a ban combining all above. This work documents the extent of children's exposure to unhealthy food advertising and the potential impact of bans. Given the ubiquity of advertising in public spaces, this New Zealand research offers innovative methods and findings likely relevant in other jurisdictions.